(untitled) (Bangladesh Journal of Medical Science, 2011)
Transmigration of mandibular canine is an unusual phenomenon characterized by movement of the impacted canine crossing the mandibular midline. Mandibular canine are rarely found impacted in a horizontal position in the mandible. Most of the time, this entity occurred as an isolated finding. However there are reports showing association of dentigerous cyst and a hyperdontia. The purpose of this report is to present a case of transmigrated canine associated with agenesis of mandibular both central incisors which is not reported previously. Key words: Intra-osseous migration; mandibular canine; agenesis; central incisors. DOI: http://dx.doi.org/10.3329/bjms.v10i2.7810 Bangladesh Journal of Medical Science Vol.10 No.2 Apr’11 pp.133-136